Chest drainage for neonatal spontaneous pneumothorax: a rare case report in a rural area - Patty, Elisabeth Ernawati; Soegianto, Sugi Deny Pranoto (Indonesian Pediatric Society, 2025)
Spontaneous pneumothorax can occur in a term neonate male through a wide variety of mechanisms, including traumatic disruption of the barriers between tissues and air, generation by infectious sources, or spontaneously through alveolar disruption. The maternal risk factor was anhydramnion with a bad obstetric history. Predisposing factors were male sex, neonate born by cesarean section, and the presence of respiratory distress syndrome. Conservative treatment was adopted for neonatal pneumothorax with mild symptoms, good general condition, and small pneumothorax. This included proper sedation, oxygen inhalation, and anti-infection therapy. If there is a presence of respiratory distress, abnormal blood gas levels, and cardiovascular instability, definitive management was evident, including expectant therapy, thoracentesis, or chest drainage. Early recognition and prompt treatment of pneumothorax were key to good outcomes in this case.